Robust Reductions of Body Weight and Food Intake by an Oxytocin Analog in Rats - Elfers, Clinton T.; Blevins, James E.; Lawson, Elizabeth A.; Pittner, Richard; Silva, David; Kiselyov, Alex; Roth, Christian L. (Frontiers in Physiology, 2021)
Background: Oxytocin is a hypothalamic neuropeptide that participates in the network of appetite regulation. Recently the oxytocin signaling pathway has emerged as an attractive target for treating obesity. However, the short half-life limits its development as a clinical therapeutic. Here we provide results from testing a long-lasting, potent and selective oxytocin analogue ASK1476 on its efficacy to reduce food intake and body weight in comparison to the native oxytocin peptide. Methods: ASK1476 features two specific amino acid substitutions in positions 7 and 8 combined with a short polyethylene glycol spacer. Short time dose escalation experiments testing increasing doses of 3 days each were performed in diet-induced overweight (DIO) male rats assessing effects on body weight as well as changes in food intake. Furthermore, DIO rats were tested for changes in body weight, food intake, temperature, and locomotor activity over 28 days of treatment (oxytocin, ASK1476, or vehicle). Results: In dose escalation experiments, significant reductions in food intake relative to baseline were detected beginning with doses of 15 nmol/kg ASK1476 (-15.2±2.3 kcal/d, p=0.0017) and 20 nmol/kg oxytocin (-11.2.9±2.4 kcal/d, p=0.0106) with corresponding significant changes in body weight (ASK1476: -5.2±0.8 g, p=0.0016; oxytocin: -2.6±0.7 g, p=0.0326). In long-term experiments, there was no difference on body weight change between 120 nmol/kg/d ASK1476 (-71.4±34.2 g, p=0.039) and 600 nmol/kg/d oxytocin (-91.8±32.2 g, p=0.035) relative to vehicle (706.9±28.3 g), indicating a stronger dose response for ASK1476. Likewise, both ASK1476 and oxytocin at these doses resulted in similar reductions in 28-day cumulative food intake (ASK1476: -562.7±115.0 kcal, p=0.0001; oxytocin: -557.1±101.3 kcal, p=0.0001) relative to vehicle treatment (2716±75.4 kcal), while no effects were detected on locomotor activity or body temperature. Conclusion: This study provides proof-of-concept data demonstrating an oxytocin analogue with extended in vivo stability and improved potency to reduce food intake and body weight in DIO animals which could mark a new avenue in anti-obesity drug interventions.